Three-dimensional quantitative margin assessment in patients with colorectal liver metastases treated with percutaneous thermal ablation using semi-automatic rigid MRI/CECT-CECT co-registration. Issue 156 (November 2022) - Faber, Robin A.; Burghout, Kimberly S.T.; Bijlstra, Okker D.; Hendriks, Pim; van Erp, Gonnie C.M.; Broersen, Alexander; Dijkstra, Jouke; Vahrmeijer, Alexander L.; Burgmans, Mark C.; Mieog, J. Sven D.
Highlights: The diagnostic ability of quantified minimal ablation margins (MAMs) is very accurate in predicting local tumour recurrence. deLIVERed co-registration software-assisted MAM assessment after thermal ablation is feasible to assess technical success. Intraprocedural scan protocols could improve quantitative MAM assessment. Abstract: Purpose: To assess the quantitative minimal ablation margin (MAM) in patients with colorectal liver metastases (CRLM) treated with percutaneous thermal ablation (TA) and correlate the quantitative MAM with local tumour recurrence (LTR). Method: Thirty-nine of 143 patients with solitary or multiple CRLM who underwent a first percutaneous TA procedure between January 2011 and May 2020 were considered eligible for study enrolment. Image fusion of pre- and post-ablation scans and 3D quantitative MAM assessment was performed using the in-house developed semi-automatic rigid MRI/CECT-CECT co-registration software deLIVERed. The quantitative MAM was analysed and correlated with LTR. Results: Eighteen (46 %) patients were additionally excluded from further analyses due to suboptimal co-registration (quality co-registration score ≤ 3). The quality of co-registration was considered sufficient in 21 (54 %) patients with a total of 29 CRLM. LTR was found in 5 of 29 (17 %) TA-treated CRLM. In total, 12 (41 %) negative MAMs were measured (mean MAM −4.7 ± 2.7 mm). Negative MAMs were significantly more frequently seen in patients who developed LTR (100 %) compared to those without LTR (29 %; p = 0.003). The median MAM of patients who developed LTR (−6.6 mm (IQR −9.5 to −4.6)) was significantly smaller compared to the median MAM of patients without LTR (0.5 mm (IQR −1.8 to 3.0); p < 0.001). The ROC curve showed high accuracy in predicting LTR for the quantitative MAM (area under the curve of 0.975 ± 0.029). Conclusion: This study demonstrated the feasibility of 3D quantitative MAM assessment, using deLIVERed co-registration software, to assess technical success of TA in patients with CRLM and to predict LTR.